2013
DOI: 10.1128/iai.00932-12
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilum Asp14 Is an Invasin That Interacts with Mammalian Host Cells via Its C Terminus To Facilitate Infection

Abstract: e Anaplasma phagocytophilum, a member of the family Anaplasmataceae, is the tick-transmitted obligate intracellular bacterium that causes human granulocytic anaplasmosis. The life cycle of A. phagocytophilum is biphasic, transitioning between the noninfectious reticulate cell (RC) and infectious dense-cored (DC) forms. We analyzed the bacterium's DC surface proteome by selective biotinylation of surface proteins, NeutrAvidin affinity purification, and mass spectrometry. Transcriptional profiling of selected ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 80 publications
5
85
0
Order By: Relevance
“…Given these observations for GFP-Rab10, we hypothesized that endogenous Rab10-positive vesicles are delivered into the ApV. Accordingly, we screened infected RF/6A cells with antibodies against endogenous Rab10 and the bacterial outer membrane protein (OMP), Asp14 (14 kDa A. phagocytophilum surface protein) (Kahlon et al ., 2013) or APH0032, which is a bacterial effector that is pronouncedly expressed late (24 to 32 h) during the infection cycle and localizes to the A. phagocytophilum occupied vacuolar membrane (AVM) (Huang et al ., 2010b). In addition to producing a vesicular labelling pattern in the cytosol and at the peripheries of ApVs, endogenous Rab10 signal surrounded individual intravacuolar bacteria in ring-like labelling patterns and partially colocalized with Asp14 signal (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these observations for GFP-Rab10, we hypothesized that endogenous Rab10-positive vesicles are delivered into the ApV. Accordingly, we screened infected RF/6A cells with antibodies against endogenous Rab10 and the bacterial outer membrane protein (OMP), Asp14 (14 kDa A. phagocytophilum surface protein) (Kahlon et al ., 2013) or APH0032, which is a bacterial effector that is pronouncedly expressed late (24 to 32 h) during the infection cycle and localizes to the A. phagocytophilum occupied vacuolar membrane (AVM) (Huang et al ., 2010b). In addition to producing a vesicular labelling pattern in the cytosol and at the peripheries of ApVs, endogenous Rab10 signal surrounded individual intravacuolar bacteria in ring-like labelling patterns and partially colocalized with Asp14 signal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous evaluation of the A. phagocytophilum surface proteome identified UMPK as a likely surface protein (Kahlon et al ., 2013). Mining the UMPK tryptic peptides recovered in that study (Kahlon et al ., 2013) revealed that they mapped to the protein’s two predicted surface-exposed regions (Fig. 9B).…”
Section: Resultsmentioning
confidence: 99%
“…phagocytophilum OMPs, OmpA and Asp14, shown to mediate entry into host cells in vitro [13, 14]. The level of conservation of these proteins was evaluated using six well-characterized A .…”
Section: Resultsmentioning
confidence: 99%
“…Unbound bacteria were removed and infection was allowed to proceed for 48 h. To determine if recombinant OmpA proteins could antagonize A. marginale infection, RF/6A cells were incubated with GST-AmOmpA, GST-ApOmpA, or GST alone (4 M) for 1 h, after which A. marginale DC organisms were added and incubated with the host cells in the continued presence of recombinant protein for 2 h. Unbound bacteria and proteins were removed and the infection was allowed to proceed for 48 h. Experiments that assessed if antibodies targeting AmOmpA or recombinant OmpA proteins could inhibit A. marginale infection of ISE6 cells were performed identically to those just described, except that A. marginale organisms were incubated with ISE6 cells for 5 h before unbound bacteria were removed, the infection was allowed to proceed for 72 h, and the MOI achieved was approximately 1.7. At the endpoint of each experiment, cells were analyzed by spinning-disk confocal microscopy to determine the percentage of infected cells and number of AmVs per cell (17,20).…”
Section: Methodsmentioning
confidence: 99%
“…Clues pertaining to the role of A. marginale OmpA (AmOmpA) are provided by recent studies demonstrating the importance of OmpA proteins to cellular invasion by A. phagocytophilum and Ehrlichia chaffeensis, two Anaplasmataceae members that cause potentially fatal infections of humans and animals (17)(18)(19). Indeed, we discovered that A. phagocytophilum OmpA (ApOmpA) is one of a trio of adhesins that cooperatively function to mediate optimal bacterial binding to and invasion of host cells (17,18,20,21). Recombinant ApOmpA binds to host cells, confers adhesiveness and invasiveness to inert beads, and acts as a competitive agonist to inhibit A. phagocytophilum infection in vitro (17,18), confirming that it alone is sufficient to mediate binding and uptake.…”
mentioning
confidence: 99%